A comprehensive evaluation of the spatiotemporal variation of CO2 and its driving forces over China - Jin, Xiaolong; Deng, Xueliang; Chen, Jian; Zhu, Song; Huo, Yanfeng; Dai, Rui; Xu, Qianqian; Cao, Ming; Wu, Yue (Frontiers in Environmental Science, 2023)
With the improved accuracy and wide coverage, satellite CO2 products could support the research of carbon sources and sinks in developing countries where the population is densely distributed and the emissions of CO2 is rapidly increased. Based on the CO2 estimates from remote sensing and atmospheric tracer transport model, this study assessed the spatiotemporal patterns of atmospheric CO2 and its driving forces over China. Results showed a consistent increasing of CO2 with a growth rate higher than 2.1 ppm/year for all levels of the troposphere. The amplitudes of seasonal variation were 1.45, 0.79, and 0.36 at the near surface, the middle and the upper troposphere. We also found a largest regional discrepancy of CO2 at the near surface for all time scales. With regard to the vertical variations, it is found that the concentrations and the change rates of CO2 at the lower troposphere are generally higher than the values at the upper troposphere. The driving mechanism analysis show that the variation of CO2 at the near surface are mainly affected by the anthropogenic and biogenic factors, which is significantly correlated to fossil fuel emissions and vegetation activities. These findings of the present study could provide a valuable reference for understanding regional carbon cycle and for formulating carbon emission reduction strategies at national scale.